À propos d’une géométrie vernaculaire : pratiques d’orientation en pays touareg - Dominique Casajus (Afriques)
What practical knowledge do the Tuareg, who have neither maps nor compasses, develop to orient and mentally situate themselves in space? This know-how is no different from what we use everyday. Our day-by-day spatial orientation has little to do with the learned description that we can make of it. This article is drawn from practices observed in northern Niger and from a study of 19th and early 20th century documents.